Facile fabrication of oxygen and carbon co-doped carbon nitride nanosheets for efficient visible light photocatalytic H2 evolution and CO2 reduction. Issue 32 (19th July 2019) - Wan, Shipeng; Ou, Man; Wang, Xinming; Wang, Yanan; Zeng, Yiqing; Ding, Jie; Zhang, Shule; Zhong, Qin
Abstract : C3 N4 nanosheets with oxygen and carbon co-doping were successfully designed for H2 evolution and CO2 reduction. A mechanistic study was also performed. Abstract : In this study, to overcome the low charge transportation efficiency and poor visible light absorption ability, and achieve highly efficient photocatalytic applications, carbon nitride nanosheets with oxygen and carbon co-doping were successfully designed and fabricated. The resultant carbon nitride nanosheets exhibited efficient photocatalytic H2 evolution and CO2 reduction performance, highlighting the efficacy of such a strategy. The highest H2 evolution rate could reach 698.43 μmol g −1 h −1, higher than that for graphitic carbon nitride (GCN). For CO2 reduction, the photocatalytic system shows a high CO selectivity, and MG3.0 achieves the largest CO generation amount of 55.2 μmol g −1 . This enhanced photocatalytic reduction performance could be attributed to oxygen and carbon co-doping, which achieves fast electron extraction and transfer, and improved visible light absorption ability. It should be noted that the excessive addition of glucose in the synthesis process could enhance conductivity and promote visible light absorption of carbon nitride, but suppress the H2 evolution and CO2 reduction ability. Simultaneously, the photocatalytic reduction mechanism is discussed. This work confirms that a carbon nitride semiconductor with oxygen and carbon co-doping could be easily prepared by this strategy, achieving efficient photocatalytic applications.